Absence of Acanthocytosis in Huntington's Disease-like 2: A Prospective Comparison with Huntington's Disease. (5th December 2017) - Anderson, David G.; Carmona, Sergio; Naidoo, Kubendran; Coetzer, Theresa L.; Carr, Jonathan; Rudnicki, Dobrila D.; Walker, Ruth H.; Margolis, Russell L.; Krause, Amanda
Background: Huntington's Disease-like 2 (HDL2) is classified as a neuroacanthocytosis; however, this remains unverified. We aim to determine if acanthocytes are present in HDL2 and whether acanthocytes can differentiate HDL2 from Huntington's disease (HD). Methods: We prospectively compared 13 HD and 12 HDL2 cases against 21 unaffected controls in Johannesburg. Blood smears were prepared using international standards and reviewed by at least two blinded reviewers. An acanthocytosis rate of greater than 1.2% in the dry smear or greater than 3.7% in the wet smear was designated a priori as the threshold for clinical significance based on previously established standards. Flow cytometry was performed on all but four of the cases. Red cell membrane protein analysis was performed on all participants. Results: There were 12 HDL2, 13 HD, and 21 controls enrolled. None of the HD or HDL2 participants had defined acanthocytosis or other morphological abnormalities. None of the HD or HDL2 cases had evidence of an abnormal band 3. Discussion: Acanthocytosis was not identified in either HDL2 or HD in our patient population. Our results, based on the first prospective study of acanthocytes in HDL2 or HD, suggest that screening for acanthocytes will not help establish the diagnosis of HD or HDL2, nor differentiate between the two disorders and raises the question if HDL2 should be placed within the neuroacanthocytosis syndromes.